(untitled) (Journal of Engineering, 2013)
Existence of these soils, sometimes with high gypsum content, caused difficult problems to the buildings and strategic projects due to dissolution and leaching of gypsum by the action of waterflow through soil mass. In this research, a new technique is adopted to investigate the performance of replacement and geosynthetic reinforcement materials to improve the gypseous soil behavior through experimential set up manufactured loaclally specially for this work. A series of tests were carried out using steel container (600*600*500) mm. A square footing (100*100) mm was placed at the center of the top surface of the bed soil. The results showed that the most effective thickness for the dune sand layer with geotextile at the interface, within the tested range, was found to be almost equal to the width of foundation. Therefore, under this depth, the soil was reinforced with geogrid and geotextile. It can be shown that (Collapse Settlement Reduction Factor) increases to (72%) when using two layers of geogrid and one layer of geotextile under depth of replacement equal to the width of footing. In addition, the results showed that the bearing capacity increases to (1.5-2.0) time under concentric loads and (2.5-3) under eccentric loads after replacement and reinforcement of gypseous soil